TSL648 : Materials development for the language classroom / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2018)
The purpose of this course is to review English Language Teaching (ELT) methods and to suggest a framework for students to evaluate and development materials for primary school. The aim is to enable primary school teachers to have the skills to adapt, adopt and create their own teaching materials as the quality of teaching will improve when teachers are able to design and match appropriate teaching materials to learners' needs.